(untitled) (Fiep Bulletin - online, 2014)
We have to be prepared for the changes. How to know that the changes will come? The solution is to create "Memoirs of the Future": the people are always making plans, dreams, sceneries, those memories are for the planning of sceneries of the future. To prepare for the future is to prepare for the maximum of possibilities and, the counted histories in the Sceneries of the Future of the Corporal Patterns of the Adolescents try to have the maximum of tuneless visions and the maximum of heterodox opinions tends in view to find the demands of the future. The sceneries are, then, small histories on possible futures of the adolescents’ corporal patterns, that you/they try to combine creativity, insight and intuition, as base for the socket of decisions in that field. Technology of the information will be the head office common to all of the defined sceneries in the four different quadrants, that contain the uncertainties in the spaces combinations reproduction and innovation - understanding and alienation. In the vertical axis, driving force reproduction & innovation and, in the horizontal axis, understanding & alienation. The axes allowed to define four different díades: reproduction & alienation; alienation & innovation; innovation & understanding and understanding & reproduction. Those díades represent dilemmas and they provide the opportunity to lift pertinent subjects and of exposing the mind the ideas and perspectives at first unthinkable. The forces that already began to act in the present moment model the sceneries that try to understand the dynamics of the future, each one delineating a different and plausible world in that can have to live and to work one day.